Above- and below-ground plant inputs both fuel soil food webs - Eisenhauer, Nico; Reich, Peter B. (Soil biology & biochemistry, 2012)
Soil food webs depend almost exclusively on plant derived resources; however, it is still subject to debate how plants affect soil biota. We tested the effects on soil decomposers of three components of soil inputs of plant species identity: presence of live plants (representing rhizodeposits), identity of shoot litter input and identity of root litter input; using all combinations of these for Trifolium pratense and Plantago lanceolata. We assessed impacts on soil microorganisms, Collembola, Oribatida and earthworms in a full-factorial greenhouse experiment. Species identity of shoot litter input had greatest effect on decomposers, following by species identity of live plant. Microbial carbon use efficiency and Oribatida density were significantly higher in the presence of T. pratense shoot litter input than in that of P. lanceolata shoot litter input, while earthworm body mass ratio was significantly higher in the presence of P. lanceolata plants than in that of T. pratense plants. Oribatida density was at minimum in the presence of P. lanceolata plants, shoot and root litter input, resulting in a significant three-way interaction and pointing to the relevance of all investigated plant input pathways. Live plant identity effects were not due to differences in living root biomass among species and treatments. Detrimental P. lanceolata effects may have been due to significantly lower N concentrations than in T. pratense tissue. Our results indicate that both above- and below-ground plant inputs into soil determine the performance of decomposers, and thus suggest due consideration of both types of inputs fueling soil food webs in future studies. ► We study the effects of live plants, shoot and root litter input on decomposer performance. ► Species identity of shoot litter input had greatest effect on decomposers. ► Oribatida density was significantly affected by a three-way interaction between plant, shoot and root litter identity. ► Above- (AG) and belowground (BG) plant inputs into soil determine the performance of decomposers. ► We suggest the consideration of both AG and BG plant inputs fueling soil food webs in future experiments.